2007
DOI: 10.1017/s0940739107070129
|View full text |Cite
|
Sign up to set email alerts
|

A Semiotics of Cultural Property Argument

Abstract: This article applies the tools of legal semiotics to examine the terms, modalities, and conventions of legal argument in the cultural property context. In a first instance, the author re-enacts Duncan Kennedy's study of recurrent patterns within legal argument to illustrate the highly structured nature of most cultural property argument. This mapping exercise shows how legal concepts draw their meaning in part from their place within a broader linguistic system, and as a result cannot by themselves form an ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…Heritage work that engages with definitions of heritage that have met no legal recognition (say, uses and definitions of heritage by Indigenous groups in countries where their customary law are not recognised by the country's settler legal system) is one instance of valid heritage work that does not directly engage with the law. Audi (2007) has suggested that -more so than in other fields -debates about the restitution of cultural heritage are held in legal terms and using the language of the law. It is a problematic statement, in that it generalises the field of HS and tries to make the law constitutive of all understandings of heritage (and the practices of the field).…”
Section: Heterodox Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Heritage work that engages with definitions of heritage that have met no legal recognition (say, uses and definitions of heritage by Indigenous groups in countries where their customary law are not recognised by the country's settler legal system) is one instance of valid heritage work that does not directly engage with the law. Audi (2007) has suggested that -more so than in other fields -debates about the restitution of cultural heritage are held in legal terms and using the language of the law. It is a problematic statement, in that it generalises the field of HS and tries to make the law constitutive of all understandings of heritage (and the practices of the field).…”
Section: Heterodox Approachesmentioning
confidence: 99%
“…It is a problematic statement, in that it generalises the field of HS and tries to make the law constitutive of all understandings of heritage (and the practices of the field). But it speaks to a concern about non-lawyers freely using legal considerations, with the unintended consequence of perpetuating orthodox legal discourses, as non-lawyers are not trained to perceive (and critique) the inherent contradictions and power structures of legal discourse in the area (Audi 2007). In a way, then, legal arguments about restitution still rely heavily on notions that put museums (colonisers) in opposition with traditional owners of artefacts (colonised), perpetuating a strand of discourse that heterodox HS has been trying to come to terms with.…”
Section: Heterodox Approachesmentioning
confidence: 99%
“…culture/property) divide. 131 However, the discussion of leading approaches to culture and property earlier illustrates that these patterns are not merely structural, they are a product of the theoretical assumptions on which dominant approaches to cultural property law are based. This potential for instrumentality becomes particularly evident when one examines the arguments that Audi argues "cluster" together.…”
Section: Critical Analysismentioning
confidence: 99%
“…. 22 These patterns emerge in response to hard cases that fall outside the easily analyzed legal problem. discussion surrounding the protection or restitution of cultural property has come to rely on a dizzying array of self-referential and self-justifying series of legal theories and counter theories."…”
Section: Introductionmentioning
confidence: 99%
“…Damit einher geht eine Naturalisierung solcher Diskurse -einschließlich der ihnen eigenen Terminologien -, die ob ihrer Eingebettetheit als unpolitisch und gegeben konstruiert werden (vgl. beispielsweise Barthes 1972:128, Hill 2008; für die Debatte um Cultural Property Audi 2007:142, Aragon und Leach 2008. Die Einbettung transnationaler politischer und ökonomischer Prozesse in moralische Diskurse kann über eine Naturalisierung hinaus zudem zur Wertaufladung bestimmter Praxen und somit zu einer (De-)Legitimierung führen (vgl.…”
Section: Fazitunclassified